(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Reactive powder concrete is a unique type of concrete with extremely high ductility and strength. To achieve the highest strength, it makes considerable use of the pozzolanic capabilities of highly reactive silica fume and Portland cement optimization. The size influence of RPC’s coefficient and law were investigated in this paper. The compressive strength of RPC is calculated using size-effect factors.